Economic Factors Affecting the Consumption of Products in Supermarkets in Luangprabang Province - Sorsingdara, Chansouda; SORSINDARA, CHANSOUDA (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study investigates the economic factors that influence consumer behavior at supermarkets in Luang Prabang. The research objectives were to examine the purchasing behavior of consumers at supermarkets in Luang Prabang, to assess the level of economic factors influencing consumer spending, and to analyze the specific economic factors affecting consumer expenditure at these supermarkets. The study surveyed a sample of 384 consumers who had previously shopped at supermarkets in Luang Prabang. Data were collected through questionnaires and analyzed using SPSS software to calculate frequencies, percentages, means, standard deviations, and to conduct multiple regression analysis. The findings revealed that most consumers primarily shop at Best-Co Minimart, with food products being the most commonly purchased items. The main reason for store selection was reasonable pricing. The most common shopping time was in the afternoon, with an average visit lasting 1–2 hours, and a shopping frequency of twice per week. Most consumers reported that their purchasing decisions were self-influenced. Average spending per visit by category was as follows: food 257,526.66 Kip; beverages 257,526.66 Kip; cosmetics 209,256.76 Kip; clothing 308,382.35 Kip; household items 279,793.81 Kip; and electronics 371,612.90 Kip. The study also found that the overall level of economic factors influencing consumer behavior was high. Individually, the levels of influence of each economic factor were also rated high. Multiple regression analysis indicated that income, expenditure, and inflation significantly affected consumer spending behavior at supermarkets in Luang Prabang, with statistical significance at the 0.05 level.